Acute Esophageal Necrosis Early after Renal Transplantation. (15th October 2021) - Makeen, Ahmad; Al-Husayni, Faisal; Banamah, Turki
Abstract : Background . Acute esophageal necrosis (AEN) is defined as a diffused black discoloration of the esophageal mucosa involving mainly the distal part of the esophagus. It is considered a rare clinical entity with a high mortality rate. The etiology of AEN is unknown, but it has been correlated to many causes such as malignancies, infections, and hemodynamics instability. Here, we report a case of a patient developing AEN a few days after kidney transplantation. Case Presentation . A 57-year-old male was admitted electively for kidney transplantation that he received from his son. The surgery was complicated with a significant drop in blood pressure but otherwise was uneventful. The patient was showing good signs of recovery but then suffered from significant hematemesis. An urgent upper esophagogastroduodenoscopy revealed black discoloration of the esophageal mucosa in keeping with AEN. The patient was treated with proton pump inhibitors infusion and started empirically on antivirals and antifungals. The patient's condition improved in regards to the AEN; nonetheless, the complications resulted in graft loss, and the patient returned to hemodialysis. Conclusion . AEN is a critical condition that mandates early intervention. Identifying high-risk populations may aid in early anticipation and diagnosis. Patients with chronic kidney disease are at risk of atherosclerosis leading to a low flow state which is exacerbated during renal transplantation surgery, especially if the procedure was complicated with a drop in blood pressure.